2013
DOI: 10.1002/trtr.1210
|View full text |Cite
|
Sign up to set email alerts
|

Fracturing Writing Spaces

Abstract: In this paper, we explore the affordances of literature‐based, arts‐infused and digital media processes for students, as multimodal practices take centre stage in an English Language Arts unit on fractured fairy tales. The study takes up the challenge of addressing multimodal literacy instruction and research in ways that utilize a range of modalities. Incorporating the perspectives and multimodal texts of five students, Alvin, Adamma, Emmett, Layla and Yacoub, we highlight the highly supportive writing enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 12 publications
0
17
0
1
Order By: Relevance
“…There has been an effort to increase children's access to technology in schools, and Lenters and Winters (2013) observed a push in the research literature for an expansion of literacy teaching beyond a focus on paper-based text construction. However, our observations in the early years are that devices (e.g., computers, laptops, iPads/tablets) are predominantly used to develop basic language and technological skills.…”
Section: Resources For Storytellingmentioning
confidence: 99%
“…There has been an effort to increase children's access to technology in schools, and Lenters and Winters (2013) observed a push in the research literature for an expansion of literacy teaching beyond a focus on paper-based text construction. However, our observations in the early years are that devices (e.g., computers, laptops, iPads/tablets) are predominantly used to develop basic language and technological skills.…”
Section: Resources For Storytellingmentioning
confidence: 99%
“…Notably, these laptops were used for multimodal composition rather than just word processing. Smaller case studies (e.g., Dalton et al, 2015; Kervin & Mantei, 2016; Lenters & Winters, 2013) have supported such gains when digital tools were used for multimodal composition with elementary students. In a fifth‐grade case study exploring multimodal storytelling with fractured fairy tales, Lenters and Winters (2013) found that multimodal composition allowed multiple entry points to literacy perhaps not available with conventional writing that were especially important for emergent bilingual students.…”
Section: Relevant Literaturementioning
confidence: 99%
“…Smaller case studies (e.g., Dalton et al, 2015; Kervin & Mantei, 2016; Lenters & Winters, 2013) have supported such gains when digital tools were used for multimodal composition with elementary students. In a fifth‐grade case study exploring multimodal storytelling with fractured fairy tales, Lenters and Winters (2013) found that multimodal composition allowed multiple entry points to literacy perhaps not available with conventional writing that were especially important for emergent bilingual students. Dalton et al (2015), in two studies with fifth‐grade students and their digital folk tale retellings, found that when using digital tools for writing, students demonstrated both “design intentionality and a metamodal awareness of how modes work together” (p. 548).…”
Section: Relevant Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…This presents a challenge for educators because students, some of whom are reluctant readers, enjoy this series immensely. Even for teachers who acknowledge texts such as Captain Underpants as engaging and humorous, the forms of humor their students would like to borrow for their own writing may be considered cheap or inappropriate (Lenters & Winters, 2013).…”
Section: Why Comedy and Humor?mentioning
confidence: 99%